Tindak Pidana Kesusilaan Ditinjau dalam Undang-Undang Darurat Nomor 1 Tahun 1951, KUHP dan KUHP 2023 - Viena Nungky Kusuma; Halif Halif; Dina Tsalist Wildana; Fanny Tanuwijaya; Laili Furqoni (LPPM Universitas Ekasakti Padang, 2023)
This article will examine the Criminal Law loophole which can still be found in the qualification of the crime of, “having intercourse with a woman out of wedlock”. In Verdict Number 30/Pid.B/2017/PN.bdw the perpetrator of crime and the victim who are both adults and without marital ties have intercourse without coercion, threats of violence and/or violence in different private areas. The Bondowoso District Court judge sentenced the perpetrator to three years in prison with a subsidiary indictment of the Public Prosecutor, namely Article 5 paragraph (3) letter b of the Emergency Law Number 1 of 1951 jo. Article 289 of the Criminal Code in Verdict Number 30/Pid.B/2017/PN.Bdw. This article will examine the accuracy of Article in Verdict Number 30/Pid.B/2017/PN.Bdw which uses Article 5 paragraph (3) letter b of the Emergency Law Number 1 of 1951 jo. Article 289 of the Criminal Code regarding the criminal act of obscenity and to examine the application of Article 412 in the new Criminal Code no. 1 of 2023 for perpetrators of criminal acts in Verdict Number 30/Pid.B/PN.Bdw.The research uses normative juridical research with statute approach and a conceptual approach.The temporary conclusion of this article is that the act of two single adults who have intercourse with the promise of marriage is still not punishable by crime. Indonesia's positive law and criminal law reforms still have legal loopholes, so they require government regulations to regulate actions that are considered morally bad. Law enforces need to take a legal sources outside of the appropriate law to convict perpetrator of criminal acts are that unequaled in the Criminal Code to fill the legal vacuum so that it does not become arbitrary space for law enforcers.